Managers and Public Hospital Performance - Muñoz, Pablo; Otero, Cristóbal (American Economic Review, 2025)
We study whether the quality of managers can affect public service provision in the context of public health. Using novel data from public hospitals in Chile, we show how the introduction of a competitive recruitment system and better pay for public hospital CEOs reduced hospital mortality by 8 percent. The effect is not explained by a change in patient composition. We find that the policy changed the pool of CEOs by displacing doctors with no management training in favor of CEOs who had studied management. Productivity improvements were driven by hospitals that recruited higher quality CEOs. (JEL D24, G34, I11, I18, J45, M54, O15)